Analisis overreaction pada saham-saham LQ-45 di Bursa Efek Indonesia - Wacana, Joshua Duta; Firdausy, Carunia Mulya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The behavior of investors as individuals in taking attitudes and actions is different in addressing information. Market participants do not all consist of rational and emotional people. In some cases, some investors behave excessively in response to information by spontaneously selling stocks when the market moves beyond expectations or buying newly profitable stocks regardless of the fundamental valuation of the stock price. Such deviations include the phenomenon of the January effect, the phenomenon size effect, and the day of the week. The overreaction hypothesis is one of the deviations that occur in the capital market. The results showed LQ-45 stocks on the Indonesia Stock Exchange despite several overreaction symptoms but showed less significant results. Based on this, it can be concluded that there is no overreaction anomaly in the stock market in the Indonesia Stock Exchange especially on LQ-45 stocks in 2013-2015. The results also show that contrarian strategies cannot be performed to obtain an abnormal return.